An Overview of Care of Young Songbirds and Waterfowl - Smith, Lisa (Wildlife Rehabilitation Bulletin, 2004)
Baby birds fall into two broad categories: altricial and precocial. Altricial babies are those that are hatched naked, blind, and completely helpless. In effect, they are still fetuses. Most songbird young fall into this category. Precocial babies are those that, shortly after hatching, can see, walk and/or swim, and self-feed. They rely on their parents primarily for protection from predators and some warmth. Most waterfowl young fall into this category. Hatchling raptors and shorebirds do not fall directly into either of these categories, but instead span a continuum between the two. One thing all baby birds have in common is that they are increasingly being affected by man’s alteration of their environment, and they need the assistance of licensed, experienced rehabilitators more and more (unfortunately). Songbirds and waterfow young are the focus of this article; each section is broken down into admission procedures, diets and feeding, husbandry, release, and post-release considerations.